Adjuvant!(©) Online estimation of chemotherapy effectiveness when added to ovarian function suppression plus tamoxifen for premenopausal women with estrogen-receptor-positive breast cancer - Paridaens, Robert J. (2010)
PURPOSE: Adjuvant! (©) Online (Adjuvant!) is a user-friendly, web-based tool that provides estimates of adjuvant therapy outcomes for individual patients. While reliable evidence underpins estimates for most patient cohorts, there is a paucity of data on the effect of adding chemotherapy to complete estrogen blockade for premenopausal women with estrogen-receptor positive breast cancer. METHODS: International Breast Cancer Study Group (IBCSG) Trial 11-93 enrolled 174 premenopausal women with estrogen-receptor positive, node-positive breast cancer. Fifty-five percent of patients had 1 positive axillary lymph node and 97% had 3 or fewer positive nodes. Patients were randomized to receive ovarian function suppression plus five years of tamoxifen with or without anthracycline-based chemotherapy. Estimated hazard rates and corresponding 10-year relapse-free survival percents obtained from Trial 11-93 data were compared with those predicted using Adjuvant!. RESULTS: The 10-year relapse-free survival percents predicted from Adjuvant! were 64.4% (95% CI, 61.9% to 67.2%) for endocrine therapy alone and 74.9% (95% CI, 73.1% to 76.8%) for chemoendocrine therapy. By contrast, these estimates in Trial 11-93 were 76.4% (95% CI, 65.8% to 84.0%) for endocrine therapy alone and 74.9% (95% CI, 64.5% to 82.7%) for chemoendocrine therapy. The Adjuvant! estimate for the endocrine alone control group is lower than that observed in Trial 11-93 (p=0.03), while the estimates for the two chemoendocrine therapy groups are similar. CONCLUSIONS: Adjuvant! appears to underestimate the effectiveness of adjuvant endocrine therapy alone for premenopausal women with endocrine responsive breast cancer, thus overestimating the added benefit, if any, from chemotherapy for this patient population.